Modulation of the nanoscale motion rate of Candida albicans by X-rays - Starodubtseva, Maria N.; Chelnokova, Irina A.; Shkliarava, Nastassia M.; Villalba, María Inés; Tapalski, Dmitry V.; Kasas, Sandor; Willaert, Ronnie G. (Frontiers in Microbiology, 2023)
Patients undergoing cancer treatment by radiation therapy commonly develop Candida albicans infections (candidiasis). Such infections are generally treated by antifungals that unfortunately also induce numerous secondary effects in the patient. Additional to the effect on the immune system, ionizing radiation influences the vital activity of C. albicans cells themselves; however, the reaction of C. albicans to ionizing radiation acting simultaneously with antifungals is much less well documented. In this study, we explored the effects of ionizing radiation and an antifungal drug and their combined effect on C. albicans. The study essentially relied on a novel technique, referred to as optical nanomotion detection (ONMD) that monitors the viability and metabolic activity of the yeast cells in a label and attachment-free manner. Our findings demonstrate that after exposure to X-ray radiation alone or in combination with fluconazole, low-frequency nanoscale oscillations of whole cells are suppressed and the nanomotion rate depends on the phase of the cell cycle, absorbed dose, fluconazole concentration, and post-irradiation period. In a further development, the ONMD method can help in rapidly determining the sensitivity of C. albicans to antifungals and the individual concentration of antifungals in cancer patients undergoing radiation therapy.